(untitled) (Global Journal of Science Frontier Research, 2015)
This study examined farmers’ perception and adoption of yam minisett technology. The study was carried out in Anambra State, Nigeria. A sample size of 120 yam farmers was used for the study. Data were collected using a structured and validated interview schedule. Data generated for the study were summarized using descriptive statistics such as frequency count, percentage and mean scores while the Sigma method was used for calculating adoption scores to ascertain the level of adoption for the various yam minisett technology items. Results of the study revealed that there were more male yam farmers (82 percent) than females. The mean age of respondents was 45years and the mean household size was 11 persons. Also, a mean farming experience of 12years was found for the respondents. Results on perception of yam minisett technology reveal that respondents had favourable perception on four statements out of the thirteen statements used to investigate their perception. These were statements 5,6,11 and 12. The remaining 9 statements were not favourably perceived. They include statements 1-4; 7-10 and 13.